Acupoint Stimulation for Fibromyalgia: A Systematic Review of Randomized Controlled Trials. (17th December 2013) - Cao, Huijuan; Li, Xun; Han, Mei; Liu, Jianping
Abstract : Background . Acupoint stimulation is popular for treatment of fibromyalgia though there is lack of comprehensive evaluation of current clinical evidence for its effect and safety. Objective . To systematically review the beneficial effects and safety of acupoint stimulation for fibromyalgia. Methods . We searched six electronic databases for randomized trials on acupoint stimulation for treatment of fibromyalgia. Two authors extracted data and assessed the trial quality independently. RevMan 5.2 software was used for data analyses with effect estimate presented as (standard) mean difference and a 95% confidence interval. We defined minimum, medium, and large SMD effect sizes as 0.3, 0.5, and 0.75. Results . 16 RCTs with 1081 participants were involved in this review. Only two trials were evaluated as low risk of bias. Meta-analysis showed that acupuncture alone or combined with cupping therapy was superior to conventional medications on reducing pain scores and/or the number of tender points. However, acupuncture showed no better than sham acupuncture on pain reduction. There was no serious adverse event reported to be related to acupoint stimulation. Conclusions . Acupoint stimulation appears to be effective in treating fibromyalgia compared with medications. However, further large, rigorously designed trials are warranted due to insufficient methodological rigor in the included trials.